Brassiere needs in relation to the physiological changes and psychosocial development of selected Filipina bra consumers - Chan, Denise Melissa B.; Lumawig, Maria Josephine Trono (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT The breast development of women differs at different ages where changes in the shape and size of the breasts occur. With this, the factors affecting brassiere purchase may differ at different ages. (Risius, et. al, 2012) as a woman's needs and motivations to wear a bra must have adjusted to her requirements. This research aimed to study the brassiere needs of Filipino women from different age groups as influenced by physiological changes and psychosocial needs. Specifically, the study aimed to determine the criteria used by women when buying brassieres and how they differ for every age group, and if women feel that their needs are met with the available brassieres in the market. Using the descriptive research method, the data was collected by means of three focus group discussions and an online quantitative survey which were used to identify the changes in brassiere needs of Filipino women from different age groups. Using the non-probability sampling technique, the study selected 18 participants for the focus group discussion and had 209 survey respondents. The top brassiere needs of selected Filipino women were similar for all age groups. These were also present in almost all physiological changes. Furthermore, the brassiere needs across the age groups based on Erik Erikson's psychosocial development did not vary where the top five brassiere needs remained the same. The ranking of the importance of the five categories was the same way across all groups: support, comfort, practicalities, psychological aspects, and aesthetics, respectively, with support scoring significantly higher than the rest among all age groups. Despite the general satisfaction of online respondents with the brassieres available in the market, the results showed that women across all age groups in the focus group discussion and survey believe that the brassieres in the market can still be improved.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Brassieres -- Philippines